Information System Management in Improving Education Services of Public Madrasah Aliyah in Jambi Province - Zostafia, Zostafia; Chatib, Adrianus; Anwar Us, Kasful (Darul Ilmi Bina Insan Foundation, 2023)
This research is motivated by the state of the state madrasah aliyah in Jambi Province. This research aims to examine the information system management in improving education services of State Madrasah Aliyah in Jambi Province. Research using a qualitative approach was conducted at the Jambi Province State Aliyah Madrasah. The main purpose of this research is to obtain scientific information as useful input for the development of information system management in improving education services of State Aliyah Madrasahs in Jambi Province. The main focus of this research is to examine the application of information systems management that uses various applications in improving educational services at State Aliyah Madrasahs in Jambi Province. The results of this study indicate that Information system management at the State Aliyah Madrasah in Jambi Province includes the stages of planning, organizing, mobilizing, controlling, coaching, and assessing.